University role and human capital - Dawood A., Al- Hidabi, Prof. Dr. (2013)
The speeches : University role and human capital, presented by Prof Dr Dawood A. Al-Hidabi, held on 12th September 2011 at Universiti Malaysia Perlis (UniMAP), Perlis, Malaysia.